Branding Stategy of Blacksmith Small and Medium Enterprise in Sukosari Village, Jember - Rokhani Rokhani; Nurul Dwi Novikarumsari; Sofia Sofia; Anik Suwandari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The community services was conducted in Sukosari Village, Jember Regency. This activity was held due to the marketing activities of SMEs in Sukosari Village are still using conventional marketing strategy, with potential markets in the Jember itself and outside cities such as Banyuwangi and Bali. The customers who have often ordered products from these subscription craftsmen, while new customers only get information by other customers. These buyers are collectors and polish craftsmen. Most of the craftsmen produce items such as knives, sickles, and wedung every day. However, there is one craftsman who specializes in producing sharp weapons with special quality as ordered by the buyer. Regarding that background, the community services team from Universitas Jember were formulated program to: Recognition of MSMEs by marking the location of the blacksmith business, which includes marking the location by marking the location on google maps for the Pandebesi MSME area in Sukosari Village, Sukowono District, Jember 2. Related assistance (Branding Development) by way of mentoring and fostering MSMEs related to digital branding Pandebesi in Sukosari Village, Sukowono District, Jember Regency. Keywords: branding, iron craft, SMSE, e-commerce